2022
DOI: 10.1002/uog.26030
|View full text |Cite
|
Sign up to set email alerts
|

Impact of rural residence and low socioeconomic status on rate and timing of prenatal detection of major congenital heart disease in a jurisdiction of universal health coverage

Abstract: What are the novel findings of this work?Of 1405 cases of major congenital heart disease (CHD), a prenatal diagnosis was made in 814. Residence in rural areas, compared with residence < 100 km from a tertiary fetal cardiology center, was associated with a 7% lower rate of prenatal diagnosis of major CHD and 19% higher rate of late diagnosis i.e. after 22 weeks' gestation. Low socioeconomic status was associated with lower prenatal-diagnosis rate in metropolitan regions and higher risk of prenatal diagnosis aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…For example, a study conducted by Kaur and colleagues explored potential barriers to prenatal diagnosis among pregnant women in the province of Alberta, Canada. Despite the Canadian healthcare system providing universal healthcare coverage, the study found that individuals in the lowest quintile of socioeconomic status had the lowest rates of prenatal diagnosis, and that when prenatal diagnosis was performed, it was often delayed (Kaur et al 2022).…”
Section: Discussionmentioning
confidence: 97%
“…For example, a study conducted by Kaur and colleagues explored potential barriers to prenatal diagnosis among pregnant women in the province of Alberta, Canada. Despite the Canadian healthcare system providing universal healthcare coverage, the study found that individuals in the lowest quintile of socioeconomic status had the lowest rates of prenatal diagnosis, and that when prenatal diagnosis was performed, it was often delayed (Kaur et al 2022).…”
Section: Discussionmentioning
confidence: 97%
“…( 19) A recent study from Alberta, Canada found that distance from a tertiary care center and lower socioeconomic status were associated with lower likelihood of prenatal diagnosis. (20) Even in places with universal health insurance, such as Canada, those of lower socioeconomic status were less likely to be prenatally diagnosed, suggesting that lower socioeconomic status has a role to play that is independent of insurance status. In our study, mothers without health insurance were less likely to have infants with prenatal diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Even within the Canadian universal healthcare system, disparities have been found in rates and timings of CHD diagnosis. Specifically, rural location is associated both with lower rates of prenatal detection and with prenatal detection occurring at a later gestational age [12].…”
Section: Location/ruralitymentioning
confidence: 99%